Hubungan Kekuatan Otot Lengan, Kelentukan Otot Punggung, dan Keseimbangan terhadap Kemampuan Lempar Tangkap Anak Usia 9-10 Tahun di Vio Surabaya - Krisna Pratama Syahlendra; Heri Wahyudi; Achmad Widodo; Noortje Anita Kumaat (Pusat riset dan Inovasi Nasional, 2025)
Age 9-10 years is a crucial stage of motor development, where physical abilities such as muscle strength, flexibility and balance significantly affect performance in sports activities, including throwing and catching skills.This study to analyze relationship between arm muscle strength, back muscle flexibility, and balance on the throwing and catching skills children aged 9–10 years at VIO Surabaya. This is quantitative research with correlational design and multiple regression analysis. The sample use 15 children (8 boys and 7 girls) who were athletes from the VIO Baseball Club Surabaya, all aged between 9-10 years. Instruments included a push-up test to measure arm muscle strength, a V-sit and reach test for back muscle flexibility, a one-leg balance test, and a throwing and catching test using a softball. The results is arm muscle strength had a significant relationship with throwing and catching skills (Pearson correlation value of r = 0.921 (p < 0.05)). In contrast, back muscle flexibility (r = 0.328) and balance (r = 0.131) did not show significant relationships. The conclution arm muscle strength is most influential factor in determining throwing and catching in children, therefore, training programs should prioritize arm strength development to support motor skill advancement in early age.